2023
DOI: 10.4254/wjh.v15.i10.1091
|View full text |Cite
|
Sign up to set email alerts
|

Progress on traditional Chinese medicine in improving hepatic fibrosis through inhibiting oxidative stress

Zhen Li,
Jun-Feng Zhu,
Hao Ouyang

Abstract: Patients with liver cirrhosis are advised to limit their sodium consumption to control excessive fluid accumulation. Salt is the most common form in which sodium is consumed daily. Consequently, various recommendations urge patients to limit salt intake. However, there is a lack of consistency regarding salt restriction across the guidelines. Moreover, there is conflicting evidence regarding the efficacy of salt restriction in the treatment of ascites. Numerous studies have shown that there is no difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 136 publications
0
0
0
Order By: Relevance
“…Blood-tonifying and blood-activating herbs that belongs to traditional Chinese medicine have shown therapeutic effects on angiogenesis-related conditions such as cardiovascular diseases and ischemiareperfusion injury in clinical practice [9,10]. Li et al extensively detailed Chinese herbs renowned for their ability to inhibit pathological angiogenesis, aiming to alleviate liver fibrosis [11]. In our review, we also reported that Fuzhenghuayu and Xuefuzhuyu significantly inhibited the dedifferentiation of LSECs, suggesting further investigation into Chinese herbs and related components regulating LSECs and their regulatory mechanisms.…”
mentioning
confidence: 99%
“…Blood-tonifying and blood-activating herbs that belongs to traditional Chinese medicine have shown therapeutic effects on angiogenesis-related conditions such as cardiovascular diseases and ischemiareperfusion injury in clinical practice [9,10]. Li et al extensively detailed Chinese herbs renowned for their ability to inhibit pathological angiogenesis, aiming to alleviate liver fibrosis [11]. In our review, we also reported that Fuzhenghuayu and Xuefuzhuyu significantly inhibited the dedifferentiation of LSECs, suggesting further investigation into Chinese herbs and related components regulating LSECs and their regulatory mechanisms.…”
mentioning
confidence: 99%